Simulations of Dielectric Frequency Response of Bushings for a Non-Destructive On-site Defect Identification - Kulandaivel, Nigalyadevi (My University, 2025)
Bushings are integrated components of high voltage transformers providing connections of windings to external circuits outside the transformer shell while providing mechanical and insulation support. During normal operation, bushings are consistently influenced by operating voltage, load current, and voltage stress due to transient over-voltages during natural or switching phenomena in the power system network. These stresses gradually degrade the bushing insulation and eventually cause failure, The insulation state should be monitored and maintained periodically. Dielectric Frequency Response (DFR) measurements yielding capacitance and loss factor values in frequency domain is one of the most popular diagnostics methods, which provides fruitful information about insulation conditions and possible defects that may be present within the bushing insulation. The aim of the thesis project is to develop a transformer bushing model using COMSOL Multiphysics to perform simulations of DFR for a real scale transform bushing geometry. The model was implemented based on electrostatics physics and current continuity through the insulation structure. The loss factor and the capacitance values were computed in the frequency window typical for practical measurements. The results of the simulations conducted using the developed model are validated by comparing them with measured DFR data. Furthermore, possible defects, which may appear in practice (conductive layers on the insulation, gas bubbles in the insulation bulk) were introduced in the model and frequency dependent loss factor and capacitance values were computed for each type of defects. The results are compared with the reference (defect free) case to identify and interpret the dielectric response behavior. The sensitivity study conducted by varying the properties of the defects indicate that the developed model provides a tool for capturing presence of defects in the insulation by analyzing changes in the DF response.
Keywords: Dissipation Factor, Dielectric Loss, Dielectric Frequency Response, Capacitance